Effectiveness of the Parenting Effectiveness Training Package on the Parent-Child Relationship in Children Aged 6 to 12 with Attention-Deficit/Hyperactivity Disorder - Iravani, Elham; Faramarzi, Salar; Rezaei jamaloei, Hasan (Applied Family Therapy Journal (AFTJ), 2024)
Objective: This study aimed to investigate the effectiveness of parenting effectiveness training on the parent-child relationship in children aged 6 to 12 with attention-deficit/hyperactivity disorder (ADHD). Method: The research employed a quasi-experimental design using a pretest-posttest framework with a control group (one experimental group and one control group). The statistical population comprised male and female students aged 6 to 12 years with ADHD in Isfahan during the 2022-2023 academic year. The research sample consisted of 32 parents and students with ADHD, who were purposefully selected and randomly assigned to the experimental and control groups. Participants were chosen based on research inclusion criteria. The Parent Effectiveness Training (PET) program included 8 training sessions for parents. Descriptive and inferential statistics were used to analyze the data. At the descriptive level, frequency tables, percentage distributions, mean, and standard deviation were calculated. At the inferential level, after verifying the assumptions for parametric testing, univariate and multivariate analysis of covariance (ANCOVA and MANCOVA) were performed. Findings: The results indicated that parenting effectiveness training had a significant effect on the parent-child relationship at the p < .05 level. Conclusion: The findings suggest that parenting effectiveness training positively influences the parent-child relationship in children aged 6 to 12 with ADHD and is an effective intervention method.